Prevalence of pulmonary hypertension in pulmonary sarcoidosis: the first large European prospective study. Issue 4 (31st October 2019) - Huitema, Marloes P.; Bakker, Annelies L.M.; Mager, Johannes J.; Rensing, Benno J.W.M.; Smits, Fokko; Snijder, Repke J.; Grutters, Jan C.; Post, Marco C.
Sarcoidosis is a systemic disease of an unknown aetiology, in which noncaseating granulomas are formed in one or multiple organs, with pulmonary involvement in >90% of the sarcoidosis patients [1]. Pulmonary hypertension (PH), defined as a mean pulmonary artery pressure of ≥25 mmHg by right heart catheterisation (RHC) [2], is a well recognised complication of sarcoidosis, associated with significant increase in mortality [3, 4]. Although the first case of PH in sarcoidosis was described in 1949 [5], the exact prevalence remains unclear. The prevalence of pulmonary hypertension in sarcoidosis seems to differ between ethnicities and was never investigated in a Caucasian cohort. This study shows a prevalence of 3% in a Caucasian cohort, significantly lower compared to other ethnicities. http://bit.ly/2kRMrap